HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU DIET PADA PASIEN DIABETES MELLITUS - Kadek Cahya Pratiwi; Ni Nyoman Ayuningsih; Elfi Kuswati; Komang Agus Jerry Widyanata (Jurnal Kesehatan Medika Udayana, 2019)
Background: Level knowledge is the result sensing human or result know someone towards an object in oder to know different once with trust, superstition, and are fallible. Where as behavior is action or deed an organism observable even learning. Diabetes Mellitus is disease metabolic to characteristic of hiperglikemia which occurs because abnormality secretion insulin, work insulin or whether both research aims to know relations level knowledge by behavior diet in patiens diabetes mellitus in Polyclinic Internal in Rumah Sakit Tingkat II Udayana. Method: This research uses descriptive correlation design with cross sectional approach, the number of samples cases wholly is 30 respondents taken by means consecutive sampling. Analyzed data in bivariat by test spearman rho. Results: The result showed that most respondent having a level knowledge enough, namely 15 people (50,0%) and behavior diet enough, namely 17 people (56,7%). The result analysis bivariat obtained value p=0,000 < ? (0,05) with price r count (0,683) > r table (0,361). Conclusion: Concluded that a significant relation exists between the level of knowledge in patiens with the diet of diabetes mellitus, where by a level close correlation coefficient is a strong positive correlation.Key words: Knowledge; Behavior; Diabetes Mellitus